Promoting ecological critical awareness through English Language Teaching: EFL teachers’ strategies and practices - Rachmawati Achadiyah (Universitas Merdeka Malang, 2025)
The increasing prominence of English has made it a marker of social status, further strengthened by the Indonesian curriculum, which maintains English as a compulsory foreign language subject. This context offers opportunities for educators, particularly English teachers, to integrate knowledge from other disciplines. While previous studies often explored cultural integration within English teaching, few have examined the incorporation of environmental issues. This study fills that gap by exploring how EFL teachers integrate environmental topics to foster students’ ecological critical awareness. Five English teachers participated through interviews and document analysis, providing evidence of classroom practices that promote such awareness. The findings reveal that teaching materials, methodologies, and learning activities play essential roles in developing students’ ecological critical awareness. Teachers frequently use videos, reading passages with visuals, and environmental vocabulary as core materials. Project-based and problem-based learning serve as key approaches, while outdoor activities—such as field visits and interviews with local communities about environmental changes—help students understand real-world ecological impacts.